Tax Havens, Foreign Ownership, and Transfer Pricing: The Moderating Role of Good Corporate Governance - Azis, Siti Nafisah (E-Jurnal Akuntansi, 2024)
This study investigates the influence of tax havens and foreign ownership on transfer pricing decisions, with a focus on the moderating role of good corporate governance. The research sample consists of manufacturing companies in the consumer goods sector listed on the Indonesia Stock Exchange (IDX) during the 2019–2022 period. The purposive sampling method was employed, resulting in a sample size of 27 companies, or 108 observations. Data analysis was conducted using Moderated Regression Analysis (MRA). The findings reveal that both tax havens and foreign ownership positively influence transfer pricing decisions. Additionally, good corporate governance moderates the relationship between tax havens and transfer pricing decisions, but it does not moderate the relationship between foreign ownership and transfer pricing decisions. This study contributes to the academic discourse on international tax policies and transfer pricing regulations. It also advances contemporary management accounting theory by providing insights into the interplay between tax strategies, ownership structures, and corporate governance mechanisms in influencing transfer pricing decisions.